PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA KEUANGAN PEUSAHAAN PADA HOTEL BERBINTANG DI KOTA MEDAN - Eka Nurmala Sari, Fitriani Saragih (Jurnal Riset Akuntansi dan Bisnis, 2009)
This research purpose to know the influence of the management controlsystem (management control structure and management control process) to thecompany’s performance at the starry hotels in Medan City both simultaneously andpartially.This research is conducted at the company of the starry hotels in Medan Cityusing census method. Data collecting done through field study by busingquestionnaire. It’s also used a library research to support this research. Dataanalysis and test of hypothesis using multiple regression analysis.The result of research indicated that: 1) The structure and process control ofmanagement have positive effect simultaneously to the starry hotel performance inMedan City. It is pointed by coefficient value or determination (R2)= 0,713. It meansthe starry hotel performance affected by structure and process control ofmanagement equal to 71,3%. It indicated that the better the structure and processmanagement control , the better the starry hotel performance. 2) The managementcontrol structure has positive effect partially to the starry hotel performance inMedan City posed through regression coefficient value equal to 0,164. It means thehigher the quality of management control structure at the starry hotel the higher thecompany’s performance. 3) The management control process partially has positiveeffect to the starry hotel performance in Medan City posed through regressioncoefficient value equal 0,313. It means the higher the quality of management controlprocess at the starry hotel the higher the company’s performance.